Unveiling educational enrollment factors in Egypt via ensemble learning - Alsheref, Fahad kamal; Mostafa El Misery, Mostafa Sayed; Bahloul, Mahmoud Mohamed; Magdi, Dalia A.; Fattoh, Ibrahim Eldesouky (Institute of Advanced Engineering and Science, 2025)
Education plays a vital role in the development of a nation and significantly influences the direction of societies. Understanding the various factors that impact educational enrollment is essential for policymakers and resource allocation strategies. This paper explores the factors impacting educational enrollment in Egypt using predictive modeling and machine learning techniques. The study evaluates six machine learning algorithms and ensemble learning approaches to predict enrollment rates, considering computational efficiency, robustness, and parameter sensitivity. By analyzing socio-economic and demographic indicators from Egyptian educational data, the research examines the interplay of these factors. Results highlight the effectiveness of these methods in elucidating enrollment patterns, with ensemble learning showing promising performance and significant improvements compared to traditional machine learning algorithms. This study offers insights into Egypt's educational landscape that could inform policy formulation and resource allocation strategies.